Improvement of the drug therapy results in patients with high blood pressure at a community pharmacy - ARIAS, JL; SANTAMARÍA-LÓPEZ, JM (Ars Pharmaceutica (Internet), 2008)
In the present work, the consequences of the sanitary assistance activity of the pharmacist in a group of patientswith high blood pressure are analyzed. The Drug Related Problems (DRP), detected in these patients at a communitypharmacy, that could generate Negative Results Associated to the Medication (NRM) were studied, carrying out aclassifi cation with respect to the pharmacotherapy qualities of necessity, effectiveness and security. The impact ofthe communication channel used in the intervention (pharmacist-patient or pharmacist-patient-doctor) in its fi nalresult was also studied. Better result was obtained when the collaboration with the doctor was selected. This studyalso remarks the need to overcome some barriers that hinders a better application of this pharmacotherapeuticmonitoring service and a greater integration of patients.